THE IMPORTANCE OF EDUCATION IN OUR DAILY LIFE. (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Education is an important issue in one’s life. It is the key to success in the future, and to have many opportunities in our life. Education has many advantages for people. For instance, it illuminates a person's mind and thinking. It helps students to plan for work, or pursue higher education by graduating from university. Having education in an area helps people think, feel, and behave in a way that contributes to their success, and improves not only their personal satisfaction but also their community. In addition, education develops human personality, thoughts, and social skills. It also prepares people for life experiences.